HUBUNGAN PENGETAHUAN IBU TENTANG KEBUTUHAN GIZI DENGAN STATUS GIZI BAYI USIA 6-12 BULAN DI KELURAHAN BATUNADUA JULU KOTA PADANGSIDIMPUAN TAHUN 2016 - Napitupulu, Mastiur (Jurnal Kesehatan Ilmiah Aufa Royhan, 2017)
Nutritional needs is the intake of food / nutrients needed by the body in order to achieve optimal growth quality. Where the best food is breast milk, but with age and growth of the baby, then the baby needs energy and substances that exceed the amount of milk. The prevalence of malnutrition in Sub BatunaduaJulu Some 25% of 40 infants. The purpose of this study was to determine the relationship of knowledge of mothers about the nutritional needs of the nutritional status of infants aged 6-12 in the Village BatunaduaJulu Year 2016. The method used is quantitative correlation with cross sectional approach. This research was conducted in the village BatunaduaJulu against the 40 mothers of infants aged 6-12 months. The analysis used were univariate and bivariate. Spearman Rho test results showed a strong correlation between the knowledge of the nutritional status of infants, with a P value <0.001 and 0.537 Significant Correlation. The study recommends maternal knowledge about nutritional needs, to be used as an indicator of nutritional status of infants.